A Fast Encoding Algorithm for Vector Quantization Using Difference Pyramid Structure - Lee, Chang-Hsing (IEEE transactions on communications, 2007)
This paper proposed a fast vector quantization encoding algorithm called difference pyramid search (DPS). According to the formation of the difference pyramid and partial distortion elimination, a rejection test inequality is derived to progressively reject a lot of nonclosest code words as early as possible. Experimental results show that the proposed DPS algorithm outperforms other pyramid-based fast search algorithms, including mean pyramid search, L2-norm pyramid search, and mean-variance pyramid search.